(untitled) (Medico Legal Update, 2020)
Indonesian liability is included as the Government’s responsibility, namely as a compulsory compliance obligation of the state or government officials or other who carry out government’s functions as a result of an objection, a law, a judicial review, which is submitted by a person, the community, an entity civil law either through court settlement or out of court. The purpose of this study was to compare the responsibilities between Indonesia Government with Netherlands. The study used juridical-normative with a comparative approach based on the statute approach as the object of discussion. This case as a form of Governments’ responsibility both in civil and administrative cases. While accountability of the Government in Netherlands (civil law system) are known with several teachings regarding civil liability, namely: Accountability based on mistakes (schuldaansprakelijkheid), liability based on an error with an inverse proof load (schuldaansprakelijkheid met omkering van de bewijslast), and liability based on risk (risicoaansprakelijkheid). In the Dutch legal system, the equivalent of strict liability is risk-aansprakelijkheid. Responsibility based on risk is a form of responsibility that is not based on the elements of error for the following activities: hazardous material management; waste management installation; and drilling mining activities. The Defendant is free from responsibility based on risk, if: loss arises as a result of war; losses due to extraordinary natural events; losses due to obeying authority orders; losses due to victim’s actions; losses due to third party actions.